Painting 1 Enoch: Biblical Interpretation, Theology, and Artistic Practice - Esler, Philip Francis (Biblical theology bulletin, 2020)
This article inaugurates a new approach to biblical interpretation that involves close collaboration on a particular text between a biblical interpreter (Philip Esler) and a practicing artist (Angus Pryor), culminating in the production of works of art that generate a new understanding of the text in question. This approach reflects the recent scholarly interest in how artists who paint biblical scenes are active interpreters of biblical texts. Here the text selected is 1 Enoch, while the artworks in question are four 2 x 2 meter paintings, in oil on canvas, that depict pivotal scenes from that text. The collaboration draws on Ethiopian tradition reflecting the scriptural status and widespread influence of 1 Enoch in Ethiopia and the fact that the complete text of the work was only preserved there until its rediscovery in modern times. The interpretative process includes a focus on the original meaning of 1 Enoch, which then influences the creation of artworks laden with theological meaning. This approach is equally available to interpreters more interested in the contemporary (rather than the historical) meaning of other biblical and extra-biblical texts where the connection with national traditions, if present, may be quite different.